Internalization Of Islamic Values In Science Education - Mustamin, Abdul Aziz bin; Wahono, Bevo (UIN Fatmawati Sukarno Bengkulu, 2020)
The study aims to increase the relative contribution of science learning to the achievement of national education goals. Internalizing the value of monotheism in scientific material will not reduce the level of scientific scholarship itself. This research is a qualitative study that is a literature study (library research) that uses books and other literature as the main object. In fact, these studies can improve the quality of science material. Science as a means to develop cognitive potential, science can also grow the potential of conscience (affective). This scientific material will be able to instill confidence in everything that exists in nature. Everything that is essentially created by God, Almighty God. This belief can drive against beliefs about submission, characteristics, and order of things that Allah created (sunnatullah), so that humans can learn them. All this will enable the growth of a positive attitude, the awe of the greatness, power, and love of God, a motivation to give thanks, increase faith and devotion to Allah Almighty. Internalization of the value of monotheism in science material can be done through the disclosure of values/wisdom/meaning/nature of the scientific material based on Islamic values